Effectiveness of Serbian health care system in 2014 - Stevanović Ivan; Gajić-Stevanović Milena (Serbian Medical Society - Dental Section, Belgrade, 2016)
The European Health Consumer Index (EHCI) is a project that since 2006 has been comparing and ranking health care systems of European countries, from the perspective of patients (consumers) - users of the health care system. Its purpose was to set standards for well functioning and organized health care. The aim of this study was to assess the state of Serbian health care system from the perspective of the European health consumer index and propose recommendations for its improvement and functioning in accordance with European standards. The assessment of the health care system is based on pre-determined forty-eight indicators divided into six groups. According to these indicators, scoring and ranking of countries was done (maximum score for a particular indicator was 3, and the minimum was 1). As per European Health Consumer Index the Republic of Serbia is ranked at 33rd place, with total of 473 points, while Netherlands has been found on the top of the list for years (this year 898 points).